2019
DOI: 10.1002/ecy.2548
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of elevational richness peaks, evaluated for trees in the east Himalaya

Abstract: Along elevational gradients, species richness often peaks at intermediate elevations and not the base. Here we refine and test eight hypotheses to evaluate causes of a richness peak in trees of the eastern Himalaya. In the field, we enumerated trees in 50 plots of size 0.1 ha each at eight zones along an elevational gradient and compared richness patterns with interpolation of elevational ranges of species from a thorough review of literature, including floras from the plains of India. The maximum number of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 67 publications
(188 reference statements)
4
29
2
Order By: Relevance
“…Seemingly contradicting this finding, fieldwork in the eastern Himalaya has shown that in small plots, herbs peak at the point where shrubs decline (Bhatta et al 2018); we also found that the decline in herbs shallows at this point (Fig. For trees, the highest over-dispersion (1700 m) is at about the line of regular freezing (White et al 2019), associated with a steep decline in the number of species that belong to primarily tropical genera (Rana et al 2019). In our dataset, the positive correlations between trees and shrubs, and between shrubs and herbs, may reflect underlying associations with benign conditions not captured by the climatic variables we studied, but alternative hypotheses based in dispersal and diversification are also possible (see below).…”
Section: Climate and Competitioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Seemingly contradicting this finding, fieldwork in the eastern Himalaya has shown that in small plots, herbs peak at the point where shrubs decline (Bhatta et al 2018); we also found that the decline in herbs shallows at this point (Fig. For trees, the highest over-dispersion (1700 m) is at about the line of regular freezing (White et al 2019), associated with a steep decline in the number of species that belong to primarily tropical genera (Rana et al 2019). In our dataset, the positive correlations between trees and shrubs, and between shrubs and herbs, may reflect underlying associations with benign conditions not captured by the climatic variables we studied, but alternative hypotheses based in dispersal and diversification are also possible (see below).…”
Section: Climate and Competitioncontrasting
confidence: 66%
“…However, temperature range, a measure of seasonality, is weakly correlated with mean temperature (r = 0.27). S5 in Rana et al 2019). S1).…”
Section: Climate Datamentioning
confidence: 94%
See 1 more Smart Citation
“…Range locations of such species are then adjusted to the nearest geometrically feasible value. Here, the assumption is that the observed extents of species are truncated subsets of actual distributions that extend beyond the domain boundary [39]. This model is similar to the range spread model where chances for species occurring at domain boundaries are much higher compared to hard boundary models [40,52].…”
Section: Geometric Constraints Modelsmentioning
confidence: 99%
“…Most studies test geometric constraints on elevational gradients using random unconstrained models with hard boundaries and the few that combine climatic predictor variables with geometric constraints also assume that all species are confined within the observed spatial extent [12,38] (but see Rana et. al [39] for a conceptual model). However, elevational extents present in most empirical data are likely to be subsets of actual geographical extents of species.…”
Section: Introductionmentioning
confidence: 99%